Kemiskinan Multidimensi Anak di Provinsi Nusa Tenggara Timur: Sebuah Analisis dengan Multiple Overlapping Deprivation Analysis - Astrid Bestari; Apriliani Gustiana (Jurnal Statistika Terapan (ISSN 2807-6214), 2023)
A child has a greater chance of experiencing poverty in his lifetime. For children, poverty means more than just a lack of money. Children who grow up in poverty tend to lack the food, sanitation, shelter, health care, and education they need to survive and thrive. This study aims to analyze the deprivation of fundamental rights of children in East Nusa Tenggara Province by applying the Multidimensional Overlapping Deprivation Analysis (MODA) framework. The data used in this analysis is socio-economic data for East Nusa Tenggara Province from the March 2022 National Socio-Economic Survey (SUSENAS). The results showed that 9 out of 10 children in East Nusa Tenggara Province were deprived of multidimensional dimensions (minimum two dimensions). Most children aged 0-4 years are deprived in five dimensions, while most children aged 5-17 are deprived in four dimensions. Children in the age group 0-4 years are deprived the most in the housing dimension. Likewise, with children in the 5-17 year age group, 8 out of 10 children in this age group live in houses with floor and wall conditions below national and international standards. When viewed from the type of area, children in rural areas are more vulnerable to deprivation than children in urban areas.